Health-Related Quality of Life and Injuries in Physical Education Students: A Multi-Group Model According to the Degree of Adherence to the Mediterranean Diet - Eduardo Melguizo-Ibáñez; José Luis Ubago-Jiménez; Daniel Sanz-Martín; José Manuel Alonso-Vargas (MDPI AG, 2024)
The Mediterranean diet is considered a healthy eating pattern. It has been shown to improve people's quality of life. When a person suffers injuries, their quality of life suffers. This research aims to accomplish the following: (a) to study the differences in the effect of the health-related quality of life on injuries according to the degree of adherence to the Mediterranean diet, (b) to analyse the existing differences in the variables that make up the health-related quality of life according to the degree of adherence to the Mediterranean diet, and (c) to analyse the degree of adherence to the Mediterranean diet according to whether the participants have suffered any injury. The study was descriptive, cross-sectional, and exploratory in a sample of 556 physical education students. The PREDIMED questionnaire, the SF-36 questionnaire, and a self-administered questionnaire were used. The results showed that high adherence to the Mediterranean diet was associated with higher quality of life and lower injury rates. It was also observed that high adherence to the Mediterranean diet improved the effect of the quality of life on injuries. In conclusion, the Mediterranean diet is beneficial for the quality of life of young university students.